The Implementation of Using Snake and Ladder Game on Speaking Program at Genta English Course Pare - Kediri - Kadnawi; Muhammad Rizal Fanani (English Teaching Journal and Research: Journal of English Education, Literature, And Linguistics, 2022)
This research is about observing to find the answer of the implementation of students’ ability. Those are (1) implementation using snake and ladder game of speaking program at Genta English Course, (2) how are the students’ responses toward using snake and ladder game at the speaking program?. In this study, the author only took one class consisting of 5 students in the speaking class. In this study, the researcher uses qualitative descriptive and the instruments used in this thesis was observation, interviews and documentation. To get the data, the researcher joins the class. The researcher describes the situation in the classroom and teaching learning process. It is used to find out if there is implementation using snake and ladder of speaking program. The results of observations, interviews and documentation conducted by researchers are about students who can be more active or more confident to speak what they want. So that students can develop their English skills much better even though there are some obstacles they get when the learning process is in the classroom. The implementation of this method is good for developing their speaking skills. The results of this study show that the snake and ladder game method is very popular with students and teachers in the class. Because this method is very easy to apply in class, especially in speaking class. By using this method. Students' abilities can develop very well. They can improve their speaking skill well. Not only improve speaking skills but also increase students' self-confidence. Keywords : Implementation, speaking, and snake and ladder game